Amazing tigers - Thomson, Sarah L.; Wildlife Conservation Society (New York, N.Y.) ([New York] : HarperCollins, 2004)
Discusses the physical characteristics, behavior, habitat, life cycle, and endangered status of tigers.
"2, reading with help."
"Wildlife Conservation Society."
590
Maine author. Sarah Thomson lives in Portland, Maine.
Keywords: Tiger -- Juvenile literature; Endangered species -- Juvenile literature